Pidana Qisas dalam Prespektif Penologi - Nafi Mubarok (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
One of the social reactions to evil is to impose criminal punishment on the perpetrator by constantly changing and perfecting what kind of punishment should be imposed by looking at the purpose of the imposition, which is the object of the study of the penology. on the other hand, in the jinayah fiqh study known qisas. This paper is present in order to describe and analyze criminal qisas, with the focus of the study in the perspective of penology. The conclusions of this paper are: first, there are at least five theories of penology, namely (1) retribution, (2) deterrence, (3) rehabilitation, (4) incapacitation, and (5) restoration. Secondly, qisas is to punish the perpetrators in accordance with their deeds, which are based on the QS. Al-Baqaarah (2): 178-179 and QS. al-Ma'idah (4): 45. Thirdly, qisas in its implementation has included five penalty theories as in penology, namely: retribution, deterence, reformation, incapacitation, and restoration.